Pengurangan Emisi CO2 dari Pemanfaatan Limbah Pelepah Kelapa Sawit pada Produksi Batako Serat - Zainuri, Zainuri; Zargustin, Dedi; Yanti, Gusneli; Megasari, Shanti Wahyuni (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTPalm oil midrib waste has not been utilized so far, so it has potentially contributed CO2Ã‚Â emissions into the atmosphere. The area of oil palm plantations in Riau province in 2015 was 2,400,900 hectares and in 2016 increased by 2,430,500 hectares. The oil palm midrib waste produced by 148 trees per hectare is 3.108 tons/month or 37.296 tons/year. It means that with 2,430,500 hectares of palm plantations, the resulting waste is 90,647,928 tons/year. The waste can affect the environment. If the palm oil midribs that have been cut and then stacked or burned will contribute large CO2Ã‚Â emissions to the environment. One of the efforts to utilize palm oil midrib waste is to use the fiber as an added material in the brick making. The purpose of this study is to calculate the reduction of CO2Ã‚Â emissions by utilizing palm oil midrib waste on fiber-brick production. The method used in this research is a descriptive method. The research carried out is quantitative with an experimental approach and laboratory research. The findings of this study are that the utilization of palm oil midrib fibers which are used as additives to the manufacture of fiber-brick concrete can reduce carbon dioxide (CO2) emissions by 231,420.06 tons/year. The conclusion of this study is that CO2Ã‚Â emissions produced from fiber-brick production machines in 1 m3 are 0.00179 ton and CO2Ã‚Â emissions that can be reduced by utilizing palm oil midrib fiber as an additive to fiber-brick production by 231,420.06 tons/year.Ã‚Â Keywords: CO2, emissions, oil palm, midribABSTRAKLimbah pelepah kelapa sawit selama ini masih belum dimanfaatkan, sehingga berpotensi menyumbangkan emisi CO2Ã‚Â ke udara. Luas perkebunan kelapa sawit yang ada di provinsi Riau tahun 2015 adalah 2.400.900 hektar dan pada tahun 2016 meningkat sebesar 2.430.500 hektar. Limbah pelepah kelapa sawit yang dihasilkan oleh 148 pohon perÃ‚Â hektar adalah 3,108 ton/bulan atau 37,296 ton/tahun. Artinya,Ã‚Â dengan luas perkebunan sawit 2.430.500Ã‚Â hektar, maka limbah yang dihasilkan sebesar 90.647.928Ã‚Â ton/tahun. Limbah tersebutÃ‚Â dapat berpengaruh terhadap lingkungan.Ã‚Â Apabila pelepah kelapa sawit yang telah dipotong lalu ditumpuk atau dibakar akan menyumbangkan emisi CO2Ã‚Â yang besar terhadap lingkungan.Ã‚Â Salah satu upaya memanfaatkan limbah pelepah kelapa sawit adalah memakai seratnya sebagai bahan tambah dalam pembuatan batako. Tujuan penelitian ini untuk menghitung pengurangan emisi CO2Ã‚Â dengan dimanfaatkannya limbah pelepah kelapa sawit pada produksi batako-serat.Ã‚Â Metode yang digunakan adalah metode deskriptif. Penelitian yang dilaksanakan bersifat kuantitatif denganÃ‚Â pendekatan eksperimental dan riset laboratorium.Ã‚Â Temuan penelitian ini adalah bahwa pemanfaatan serat pelepah kelapa sawit yang dijadikan sebagai bahan tambah pada pembuatan batako-serat dapat mengurangi emisi karbon dioksida (CO2) sebesar 231.420,06 ton/tahun.Ã‚Â Kesimpulan penelitian ini adalah bahwa emisi CO2Ã‚Â yang dihasilkan dari mesin produksi batako-serat dalam 1 m3Ã‚Â adalah 0,00179 ton/m3Ã‚Â dan emisi CO2Ã‚Â yang dapat dikurangi dengan memanfaatkan serat pelepah kelapa sawit sebagai bahan tambah pada produksi batako-serat sebesar 231.420,06 ton/tahun.Kata kunci: CO2, emisi, kelapa sawit, pelepah